Effect of Sphagnum biomass aqueous extracts on Lepidium sativum ‘Cresso’ seed germination - Irrgang, Stefan; Blievernicht, Armin; Stark, Timo D.; Ulrichs, Christian; Förster, Nadja (Frontiers in Horticulture, 2026)
Sphagnum biomass (SBM) is a predecessor of peat and may be the most promising candidate for replacing peat in horticultural growing media. It is the only organic, regrowing material that shares decisive physical and chemical features with peat, which remains the undisputed reference material in horticultural growing media production and use. Despite multiple experimental confirmations of the applicability of SBM for growing media, scattered reports of growth inhibition in plants grown in SBM raise concerns that allelopathic effects may derive from this material. To attribute and quantify potential growth inhibition, a broad sample set of SBM was collected, processed as aqueous extracts (AESBM), and applied to seeds of Lepidium sativum ‘Cresso’ in a series of laboratory plant assays. The majority of extracts induced significant inhibitory effects on germination and early growth. Using HPLC–MS, secondary metabolites (phenolics) were determined qualitatively and quantitatively. Thirty-eight SBM samples obtained from Sphagnum farming sites and greenhouse-grown material were analyzed. A group of compounds occurred in all samples, defining a core set of phenolic compounds. The complexity of the compound mixture in AESBM did not allow a clear attribution of the observed effects to individual substances; however, machine learning–based feature selection and importance analysis revealed a clear contribution of two detected compounds. Heat treatment of SBM at 60 and 80 °C significantly reduced the inhibitory effects of the material. Further studies should apply fractionation approaches to evaluate the effects of specific compounds individually.